2021
DOI: 10.21037/apm-21-276
|View full text |Cite
|
Sign up to set email alerts
|

Early integrated palliative care for haematology cancer patients-the impact on symptom burden in Hong Kong

Abstract: Background: Evidence showed that early palliative care could have many benefits in clinical outcomes for patients living with advanced medical illnesses. In fact, most of these studies have not involved patients with advanced haematologic cancer (HC), which are known to be associated with significant physical and psychological symptoms. In Hong Kong, an Early Integrated Palliative Care (EIPC) collaboration involving both Heamatology unit of Queen Mary Hospital (QMH) and the Palliative Medical Unit of Grantham … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…It is increasingly understood that people with haematological cancers may have unmet palliative care needs and that there can be uncertainty about the optimal timing of palliative care in the patient journey [ 40 ]. It has been suggested that an understanding of the unique trajectories of people with haematological cancers is needed by specialist palliative care teams [ 41 ] and also that early, integrated palliative care alongside haematology treatments can be beneficial, with improved physical and psychological symptom control amongst other benefits [ 42 ]. A collaborative approach, both within multidisciplinary haematology teams, but also between haematology and specialist palliative care teams, has been proposed [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly understood that people with haematological cancers may have unmet palliative care needs and that there can be uncertainty about the optimal timing of palliative care in the patient journey [ 40 ]. It has been suggested that an understanding of the unique trajectories of people with haematological cancers is needed by specialist palliative care teams [ 41 ] and also that early, integrated palliative care alongside haematology treatments can be beneficial, with improved physical and psychological symptom control amongst other benefits [ 42 ]. A collaborative approach, both within multidisciplinary haematology teams, but also between haematology and specialist palliative care teams, has been proposed [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized controlled trials have demonstrated the benefits of concurrent specialty palliative care (PC) with oncologic care, with enhanced patient outcomes such as better quality of life and mood (1)(2)(3)(4)(5). Early supportive care is also associated with improved clinical symptoms and less intensive end-of-life interventions (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…According to World Health Organization (WHO), palliative care (PC) could improve the symptom and psychosocial aspects of patients with advanced medical illness (1). Early PC had been shown to improve symptom burden, quality of life and other clinical outcomes in advanced cancer patients (2)(3)(4).…”
mentioning
confidence: 99%
“…The authors speculated that misconceptions on the purpose of PC and the timing for referral, thus might have led to a delay to specialty PC for patients who received multiple prior palliative chemotherapy regimens at EOL. It is recommended that two or more lines of palliative chemotherapy could be a trigger for early specialty PC referral as to facilitate advance care planning discussions which could reduce use of some of unnecessary EOL treatments e.g., chemotherapy (2). Much work still has been done to improve the timing for early PC.…”
mentioning
confidence: 99%
See 1 more Smart Citation